Minimally invasive repair of a lumbar hernia utilizing the subcutaneous space only. Issue 4 (2nd October 2019) - Clothier, Jessica S.; Ward, Marc A.; Ebrahim, Ahmed; Leeds, Steven G.
Abstract: Lumbar hernias are from weakened areas in the posterior lateral abdominal wall. Minimally invasive techniques are recommended for nonmidline abdominal wall hernias. Endoscopic methods utilizing the subcutaneous space only are rarely reported. A 66-year-old man presented with abdominal pain and a computed tomography (CT) scan revealing a lumbar hernia. The procedure was done utilizing the subcutaneous space to open the hernia sac and repair the defect in layers. A sublay mesh and an onlay mesh were used within the subcutaneous pocket. The patient had an uneventful postoperative course and was discharged home. A subsequent CT scan showed that the completed repair remained intact. Few endoscopic lumbar hernia repairs are reported despite the advantageous aspects of the procedure in avoiding the peritoneal cavity and the retroperitoneum.